Pendampingan Manajemen Layanan dan Usaha Berorientasi Clean and Healthy Pada Pedagang Kaki Lima Sekitar Wisata Desa Hendrosari Kecamatan Menganti Gresik - Asep Saepuloh; Ahmad Qoni Dewantoro; Sukaris Sukaris (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
At this time, the important role of Pedagang Kaki Lima (PKL) is felt in supporting the increase in family income, especially during the pandemic, because the economic situation affected is so broad and provides challenges and hopes to keep trying in a situation of limiting restrictions and implementing health protocols during the pandemic. Situations like this also happen to street vendors around Lontar Sewu Gresik Tourism, because after all the high and low sales of street vendors will also depend on the number of visitors to tourist sites, the more visitors there are, the higher the potential for purchases of street vendors who are around tourist sites. The problem that occurs in cooperative street vendors is that the priority activities to be carried out are business management issues, including marketing and service management and business management oriented to the implementation of health protocols. The initial study that we found in the field during our observations was that there was still traditional business management (how to sell, business packaging) services through communication that were still sales-oriented, not customer-oriented, and had not implemented health protocols optimally in their sales activities. The plan for this activity is to strengthen the capacity of service and business management that is oriented towards cleanliness and health during the COVID-19 pandemic